Digital Piety and Audiovisual Interpretation of the Qur’an: A Critical Discourse Analysis of the @Jedanulis YouTube Channel - Cindy Dea Anggraini; Ahmad Zaidanil Kamil (Journal of Digital Islamic Thought, 2026)
Generation Z’s deep immersion in digital culture often engenders existential anxiety and mental health vulnerabilities shaped by performativity and hedonistic self-presentation. This study examines how the YouTube channel @Jedanulis, managed by Habib Husein Ja’far al-Hadar, responds to these dynamics through the audiovisual interpretation of the Qur’an. Employing Teun A. van Dijk’s Critical Discourse Analysis, the article explores how the channel synthesizes Islamic theology with insights from modern psychology to reconstruct the notion of “digital piety.” The findings demonstrate that @Jedanulis functions simultaneously as a diagnostic and prescriptive platform, reframing rigid religious discourse into inclusive narratives that address distinct digital pathologies, including alienation and the pursuit of symbolic validation. This study's primary contribution lies in reconceptualizing audiovisual interpretation not merely as a medium of religious transmission, but as a critical instrument of social reflection. It argues that @Jedanulis promotes a shift from passive digital consumption toward reflective self-sovereignty, advocating a balanced (wasaṭīyah) mode of digital existence. By doing so, this research extends the field of digital religion by illustrating how new media can enable dialogical and therapeutic engagement with scripture.